Improving Sanitation in Cold Regions : Catalog of Technical Options for Household-Level Sanitation - Leblanc, Maryanne; Reed, Robert A.; Kingdom, William; Gambrill, Martin; Rodriguez, Diego Juan (World Bank, Washington, DC, 2019)
Globally, 2.5 billion people lack access to improved sanitation. Improving sanitation is a challenge around the world; cold climates add to that challenge. The objective of this Catalog is to identify suitable technological options for delivering sustainable improved sanitation in cold regions where the population is not served by piped water supply and sewer networks.